How Does Generation Z Pay Zakat - Nur Zaroni, Akhmad (Journal of Management, 2024)
The purpose of this study is to examine the factors that affect Generation Z's propensity to pay zakat using digital means. This study falls under the category of descriptive qualitative research utilising the library research technique; specifically, it involves a review and reanalysis of earlier studies on the connection between generation Z's behavioural intention to pay zakat and the digitisation of zakat. Previous scientific research journals were used as data sources, which were subsequently processed and analysed through the use of data reduction, data display, and verification. According to the analysis's findings, generation Z's intention to use digital zakat to pay zakat is significantly influenced by convenience and ease of use. Meanwhile, generation Z's intention to use digital zakat to pay zakat is not significantly influenced by religiosity. It is hoped that future research will be able to look more broadly at the issues that this study was unable to cover.